Morphological characteristics of soft coral Sarcophyton serenei (Tixier-Durivault, 1958) in Nha Trang Bay - Lam, Ho Son; Nguyen Thi Nguyet, Hue; Dao Thi Hong, Ngoc; Dang Tran Tu, Tram; Nguyen Cong Nhat, Nhat; Hua Thai, An; Ho Thi, Hoa; Thai Minh, Quang; Hoang Xuan, Ben; Dao Viet, Ha; Nguyen Thi Anh, Thu; Dinh , Truong An (Vietnam Journal of Marine Science and Technology, 2025)
Soft corals are integral components of tropical coral reef ecosystems, contributing significantly to biodiversity and providing substantial economic value as ornamental organisms and sources of bioactive compounds. As such, accurate classification of soft coral species is essential for the sustainable management and exploitation of these resources. Sarcophyton serenei, a soft coral species found in Nha Trang Bay, is commercially important for the marine ornamental trade and the extraction of bioactive substances. This species is characterized by a bright yellow-brown to gray-brown coloration, short and semi-contracted polyps, and a smooth capitulum with numerous folds along the periphery of the disc. The surface of the disc is rough and lacks mucus secretion, distinguishing it from other species in the genus Sarcophyton. The morphological characteristics of the sclerites, including those from the anthocodiae, tentacles, capitulum, and stalk were examined and found to match the descriptions provided by Tixier-Durivault (1958) and Dautova & Savinkin (2013), with some minor differences from the classification key of Verseveldt (1982). Scanning electron microscopy (SEM) was applied to study the surface features of the sclerites, revealing detailed structures such as warts, spines, and granules. Additionally, rDNA ITS2 sequencing was used to identify the coral’s algal endosymbionts, which belongs to the genus Symbiodinium, specifically clade C. The nucleotide sequence analysis showed minimal variation among the symbionts, indicating a high degree of similarity within this clade. These findings contribute to the broader understanding of S. serenei and its ecological role in coral reef ecosystems, while also supporting the need for effective conservation and sustainable utilization strategies.